Blob distortion by radio-frequency induced sheared flow. (5th June 2019) - Zhang, W.; Cziegler, I.; Bobkov, V.; Conway, G.D.; Fuchert, G.; Griener, M.; Kardaun, O.; Manz, P.; Noterdaeme, J.-M.; Seliunin, E.; Wolfrum, E.
Abstract: Blob transport properties in the plasma edge in the presence and absence of radio-frequency (RF) convective cells are compared. For the first time, the interactions between RF convective cells and intermittent plasma blobs in the scrape-off layer (SOL) are observed with gas puff imaging in the ASDEX Upgrade tokamak. It is found that the RF convective cells induce a sheared flow in the far SOL, which is able to stretch, distort and even split the blobs poloidally. The observed phenomena indicate that an externally generated sheared flow in the SOL can be considered as a method to modify blob transport in a favorable way.